2020
DOI: 10.1038/s41586-020-3027-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the oocyte transcriptional network with transcription factors

Abstract: During female germline development oocytes become a highly specialized cell type, and form a maternal cytoplasmic store of crucial factors during oocyte growth. Oocyte growth is triggered at the primordial-primary follicle transition accompanied with dynamic changes in gene expression 1 , yet the gene regulatory network underpinning oocyte growth remains elusive. Here we identified a set of transcription factors sufficient to trigger oocyte growth. By dissection of the change in gene expression and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 60 publications
3
102
0
Order By: Relevance
“…Recent progress in the field of in vitro gametogenesis (IVG) has had a great impact on reproductive biology and medicine ( Hikabe et al, 2016 ; Hamazaki et al, 2021 ). Fully developed oocytes can now be obtained from embryonic stem cells or induced pluripotent stem cells of mice by the application of IVG techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in the field of in vitro gametogenesis (IVG) has had a great impact on reproductive biology and medicine ( Hikabe et al, 2016 ; Hamazaki et al, 2021 ). Fully developed oocytes can now be obtained from embryonic stem cells or induced pluripotent stem cells of mice by the application of IVG techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has reported the generation of functional gametes from iPSCs in mouse [20], and key PGC developmental pathways have been identified in human [21,53,54] and cynomolgus monkey [44]. Recently, transcription factor-driven oocyte development from PSCs has been reported [55].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, relative expression levels of some of Figla downstream genes were significantly different between secondary follicle oocytes of pre-/mature mice, supporting that secondary follicle growth in mature mice may be regulated in part by Figla. However, as folliculogenesis is a highly complex process 48 that requires appropriate set of genes to orchestrate its growth 49 , there is a limitation for discussing it with a single transcription factor.…”
Section: Discussionmentioning
confidence: 99%